2020
DOI: 10.1016/j.ijsu.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The socio-economic implications of the coronavirus pandemic (COVID-19): A review

Abstract: The COVID-19 pandemic has resulted in over 1.4 million confirmed cases and over 83,000 deaths globally. It has also sparked fears of an impending economic crisis and recession. Social distancing, self-isolation and travel restrictions forced a decrease in the workforce across all economic sectors and caused many jobs to be lost. Schools have closed down, and the need of commodities and manufactured products has decreased. In contrast, the need for medical supplies has significantly increased. The food sector h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
4,287
1
241

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 5,669 publications
(5,009 citation statements)
references
References 4 publications
46
4,287
1
241
Order By: Relevance
“…As of August 6th, 2020, the COVID-19 pandemic has infected 18,956,836 people and killed over 710,053 worldwide (https://www.worldometers.info/coronavirus/). The pandemic has caused economic shutdown in many countries, fears of a global recession, restricted travel, closure of educational institutions, and mental distress on a global level [8][9][10]. With the drastic widespread and impact of SARS-CoV-2, many countries are still fighting against the first wave of the virus and fear the devastation of future waves [11].…”
Section: Introductionmentioning
confidence: 99%
“…As of August 6th, 2020, the COVID-19 pandemic has infected 18,956,836 people and killed over 710,053 worldwide (https://www.worldometers.info/coronavirus/). The pandemic has caused economic shutdown in many countries, fears of a global recession, restricted travel, closure of educational institutions, and mental distress on a global level [8][9][10]. With the drastic widespread and impact of SARS-CoV-2, many countries are still fighting against the first wave of the virus and fear the devastation of future waves [11].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) has had enormous socioeconomic impact 1 . In 5 months, 5.5 million COVID-19 cases have been confirmed, resulting in 350,000 deaths across 188 countries 2 .…”
Section: Mainmentioning
confidence: 99%
“…In view of the above motivation, the current study look at the performance of the pharmaceutical industries, especially those associated with the production of vitamins and other immune-related drugs in the framework of the United States' COVID-19 situation. Although Nicola et al (2020) and Mason-D'Croz et al (2020) have earlier suggested the likelihood of spillover effect of the COVID-19 pandemic to the socio-economic aspects, there is no study that specifically noted a pharmaceutical sector-specific effect from the nCOVID-19 pandemic. Hence, the novelty of the current study is that it offers a highlight of a few important contribution to the existing nCOVID-19 literature in a unique pattern.…”
Section: Introductionmentioning
confidence: 97%